Review of African swine fever outbreaks history in South Africa: From 1926 to 2018 - (:unkn) unknown (My University, 2021)
The article reviews the outbreaks and distribution of African swine fever (ASF) in South Africa since the first probable outbreak that occurred in the Koedoesrand Ward in 1926. Retrospective data on the ASF outbreaks in South Africa were obtained from the World Organisation for Animal Health (OIE) disease database and the South African veterinary services annual reports in addition to published articles and online sources. South Africa has experienced many outbreaks that can be divided into 2 time periods: the period before the development of the OIE diseases database (1993) and the period after. More than 141 outbreaks of ASF were reported during the first period. Since the development of OIE disease database, 72 outbreaks directly involving 2968 cases, 2187 dead and 2358 killed pigs mainly in smallholder pig farms were reported. The median number of cases for a given ASF outbreak is 17, but in 50% of outbreaks no pigs were killed for prevention. The most important ASF outbreak was reported in April 2014 in the Greater Zeerust district (North West province) involving 326 cases and 1462 killed pigs. However, the outbreak with highest mortality involving 250 pigs was reported in 2016 (Free State province). According to phylogenetic analysis, nine p72 genotypes (I, III, IV, VII, VIII, XIX, XX, XXI and XXII) have been identified in South Africa. Season-wise, more outbreaks were recorded during summer. It was also observed that the OIE disease database could contain errors that would have been introduced through compiled forms at country level. Spatiotemporal studies on ASF outbreaks in South Africa are therefore required in order to assess statistically and quantitatively the clustering of outbreaks over space and time.
Keywords: African Research